L1 interference in English major students’ pronunciation at Technical University of Cotopaxi. - Pupiales Yepez, Janeth Patricia (2023)
This research aims to investigate the impact of mother tongue interference (Spanish) on the pronunciation of the phoneme /d/ across different positions among seventh-semester students enrolled in the English Major at the Technical University of Cotopaxi. The study employs a mixed-method approach with a descriptive correlational design. The data collection process involved five stages: Pronunciation Recordings, Qualitative Analysis, Quantitative Analysis, Comparison with Standard English, and Validation and Interpretation. The independent variable is the interference of L1 (mother tongue), while the dependent variable is the pronunciation of students. The findings of the study shed light on the challenges faced by students when pronouncing words with the phoneme /d/ in different positions. In the initial position, the interference is characterized by the transference of Spanish tongue positions and aspiration tendencies, leading to the production of [d] instead of the standard English sound. In the middle position, students exhibit a tendency to apply Spanish flapping and elision patterns, resulting in the articulation of a tap or alveolar flap [ɾ] instead of the expected English sound. Finally, in the final position, the influence of Spanish leads some students to voice the English final /d/ even when English requires voicelessness, indicating the persistence of L1 interference. These results emphasize the importance of addressing specific phonetic and phonological challenges that arise due to mother tongue interference in pronunciation training. Pedagogical strategies should be developed to address these issues and guide students toward more accurate English pronunciation, particularly in the context of the Technical University of Cotopaxi. Understanding the intricate interplay between L1 influence and the articulation of the phoneme /d/ can lead to targeted interventions that enhance students' pronunciation skills and contribute to their overall communicative competence in English.